2017
DOI: 10.4238/gmr16029662
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of plant growth-promoting bacteria associated with sugarcane

Abstract: ABSTRACT. The sugarcane (Saccharum spp) presents economic importance, mainly for tropical regions, being an important Brazilian commodity. However, this crop is strongly dependent on fertilizers, mainly nitrogen (N). This study assessed the plant growth-promoting bacteria (PGPB) associated with sugarcane that could be used as a potential inoculant to the crop. We evaluated the genetic diversity of PGPB in the plant tissue of sugarcane varieties (RB 867515, RB 1011, and RB 92579). The primer BOX-A1R was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
1
12
0
1
Order By: Relevance
“…However, the phyla of these genera have also been reported many times in other sugarcane soil studies. Acidobacteria and Actinomycetes are also more common in sugarcane soils treated with nitrogen fertilizer [ 54 , 55 ]. Proteobacteria significantly increased in bagasse mulching sugarcane soil [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the phyla of these genera have also been reported many times in other sugarcane soil studies. Acidobacteria and Actinomycetes are also more common in sugarcane soils treated with nitrogen fertilizer [ 54 , 55 ]. Proteobacteria significantly increased in bagasse mulching sugarcane soil [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…And several species of Methylobacterium have been reported as plant growth-promoting bacteria (PGPB) and Hg-resistant bacteria (Durand et al 2017;Antunes et al 2017;Grossi et al 2020). In addition, Tani et al (2015) found that Methylobacterium can not only use methanol emitted by plants as a carbon source and energy source, promote plant maturity, increase particle size, but also show super-strong species level on a given plant species Selection pressure is critical to achieving growth promotion.…”
Section: The Venn Diagram Data (Supplementarymentioning
confidence: 99%
“…The promotion of plant growth by PGPB is already known and it involves, among others, biochemical capabilities, production of phytohormones such as indole-3-acetic acid (IAA) and the process of biological nitrogen fixation (Souza et al 2015). Indeed, these PGPB isolates presented a high capability of producing IAA and performing the biological N fixation in sugarcane (Antunes et al 2017), and could also promote the maize and sorghum growth. Previous studies have shown positive growth responses in maize and sorghum, when inoculated with PGPB (Schlemper et al.…”
Section: Resultsmentioning
confidence: 99%
“…The study was conducted at the Universidade Federal do Piauí, in Teresina, Piauí state, Brazil, from March to June 2018. A total of 40 PGPB isolates (Table 1), obtained in leaves and stalks of sugarcane by Antunes et al (2017), were inoculated into seeds of sorghum (Sorghum bicolor cv. Palo Alto N52K1009) and maize (Zea mays cv.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation